The level of internet financial reporting of Malaysian Companies - Mohd Noor Azli Ali Khan,; Noor Azizi Ismail, (FEP, 2011)
This research analyses the issue of the level of Internet financial reporting (IFR) by companies listed on the Main Board of Bursa Malaysia. The discussion in this paper will be based on the inconsistencies of the dimensions used in representing IFR by previous researchers who had carried out studies on IFR. The inconsistencies resulted in differences in their findings. Based on a comprehensive review, the level of IFR for this research will be divided into two main dimensions, namely, content dimension and presentation dimension. The findings showed that the level of IFR of Bursa Malaysia listed companies started from 48.27 per cent to 78.16 per cent with a min of 65.10. The findings also showed that the overall level of IFR listed companies on the Main Board of Bursa Malaysia was considered good. The implication of the research findings and future research will also be discussed.